Wnt Signaling Through Nitric Oxide Synthase Promotes the Formation of Multi-Innervated Spines - McLeod, Faye; Boyle, Kieran; Marzo, Aude; Martin-Flores, Nuria; Moe, Thaw Zin; Palomer, Ernest; Gibb, Alasdair J.; Salinas, Patricia C. (Frontiers in Synaptic Neuroscience, 2020)
Structural plasticity of synapses correlates with changes in synaptic strength. Dynamic modifications in dendritic spine number and size are crucial for long-term potentiation (LTP), the cellular correlate of learning and memory. Recent studies have suggested the generation of multi-innervated spines (MIS), in the form of several excitatory presynaptic inputs onto one spine, are crucial for hippocampal memory storage. However, little is known about the molecular mechanisms underlying MIS formation and their contribution to LTP. Using 3D enhanced resolution confocal images, we examined the contribution of Wnt synaptic modulators in MIS formation in the context of LTP. We show that blockage of endogenous Wnts with specific Wnt antagonists supresses the formation of MIS upon chemical LTP induction in cultured hippocampal neurons. Gain- and loss-of-function studies demonstrate that Wnt7a signalling promotes MIS formation through the postsynaptic Wnt scaffold protein Dishevelled 1 (Dvl1) by stimulating neuronal nitric oxide (NO) synthase (nNOS). Subsequently, NO activates soluble guanylyl cyclase (sGC) to increase MIS formation. Consistently, we observed an enhanced frequency and amplitude of excitatory postsynaptic currents. Collectively, our findings identify a unique role for Wnt secreted proteins through nNOS/NO/sGC signalling to modulate MIS formation during LTP.